Association of comorbidities in atrial fibrillation in acute myocardial infarction - Ahamed H.B., Irfan; Abdullah, Bilal Bin; Ismail, Mohammed; Jagirdar, Syed Aman (International Journal of Advances in Medicine, 2017)
Background: Atrial fibrillation is a most common arrhythmia in patients with and without structural heart disease with an increasing incidence mainly due to the aging population. As the population ages, one can expect that AF will remain a frequent and troublesome complication of AMI with comorbidities. Therefore, the present study was undertaken to investigate the association of co-morbidities in atrial fibrillation in acute myocardial infarction. Methods: The study was performed after the institutional ethical clearance and consent from all the patients. Heart rate, atrial fibrillation, blood pressure, ventricular fibrillation and stroke after acute myocardial infarction were recorded. The blood sugar and serum lipid levels were also measured using commercially available kit as per the manufacturer’s guidelines. The data was analyzed for statistical significance using univariate analysis and comparison was performed by Fisher Exact test and by using SPSS Version 20. Results: In our study, all the patients who developed AF after AMI were more than 60 years of age. Higher heart rate was more than or equal to 100 in 62.5% of the patients. 25% of patients had diabetes mellitus 75% of 8 patients had atrial fibrillation after acute myocardial infarction, 77% of patients without atrial fibrillation were known hypertensive’s. Out of the patients who had atrial fibrillation, 50% had hyperlipidemia and developed ventricular fibrillation. Conclusions: Higher heart rate (>100 bpm) at time of presentation is a risk factor for AF following to AMI. Patients with new onset AF after AMI had more complication during hospital stay.